Integrative genomic and network analysis identified novel genes associated with the development of advanced cervical squamous cell carcinoma - Roychowdhury, Anirban; Samadder, Sudip; Das, Pijush; Mandloi, Sapan; Addya, Sankar; Chakraborty, Chandraditya; Basu, Partha Sarathi; Mondal, Ranajit; Roy, Anup; Chakrabarti, Saikat; Roychoudhury, Susanta; Panda, Chinmay Kumar (Biochimica et biophysica acta. General subjects, 2017)
CSCC is one of the most common cancer affecting women globally. Though it is caused by the infection of hrHPV but long latency period for malignant outcome in only a subset of hrHPV infected women indicates involvement of additional alterations, primarily CNVs. Here, we showed how CNVs played a crucial role in development of advanced tumors (stage III/IV) in Indian patients. Initially, high-resolution CGH-SNP microarray analysis pointed out frequent CNVs followed by significantly altered genes. After comparison with TCGA dataset, expressions of the genes were checked in three CSCC datasets to identify key genes followed by Ingenuity® Pathway analysis. Then node effect property analysis was applied on the constructed PPI network to rank the key proteins. Finally, validations in independent samples were performed. For the first time, frequent chromosomal amplifications at 3q13.13–3q29, 1p36.11–1p31.1, 1q21.1–1q44 and 5p15.33–5p12 followed by common deletions at 11q14.1–11q25, 2q34–2q37.3, 4p16.3–4p12 and 13q13.3–13q14.3 were identified in Indian CSCC patients. Integrative analysis found 78 key genes including several novel ones, which were mostly associated with ‘Cancer’ and may regulate DNA repair and metabolic pathways. Analysis showed PARP1 and ATR were among the top ranking protein interactors. Frequent amplification and over-expression of ATR and PARP1 were further confirmed in cervical lesions, indicating their association with poor prognosis of advanced CSCC patients. Our novel approach identified precise CNVs along with several novel genes within these loci and showed that PARP1 and ATR, having biologically significant interactions, may be involved in development of advanced CSCC. [Display omitted] •Cervical squamous cell carcinoma (CSCC) is one of the most frequent cancers among women worldwide.•Unique strategy followed by validation to understand the role of CNVs in the development of advanced cervical carcinoma•High-resolution CGH-SNP microarray to identify precise CNVs in Indian patients for the first time•Novel PPI network based analysis to locate proteins having biologically significant interactions•Amplification and over-expression of PARP1 and ATR may play a role in development of advanced CSCC having poor prognosis.